2008
DOI: 10.1063/1.2956398
|View full text |Cite
|
Sign up to set email alerts
|

Chromium and tantalum site substitution patterns in Ni3Al(L12) γ′-precipitates

Abstract: The site substitution behavior of Cr and Ta in the Ni 3 Al ͑L1 2 ͒-type ␥Ј-precipitates of a Ni-Al-Cr-Ta alloy is investigated by atom-probe tomography ͑APT͒ and first-principles calculations. Measurements of the ␥Ј-phase composition by APT suggest that Al, Cr, and Ta share the Al sublattice sites of the ␥Ј-precipitates. The calculated substitutional energies of the solute atoms at the Ni and Al sublattice sites indicate that Ta has a strong preference for the Al sites, while Cr has a weak Al site preference. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(35 citation statements)
references
References 28 publications
5
28
1
1
Order By: Relevance
“…The average width of the c regions between c 0 , also known as c channels, is 30-40 nm. Atomic-resolution EDS, in Figure 1(b), reveals that Cr predominantly occupies the Al sub-lattice in the c 0 phase, in agreement with recent atom probe tomography experiments 15,16 and first-principles calculations. 17 At the atomic scale, a representative c 0 /c interface is shown in Figure 1(c), where the two regions can be distinguished by the presence of the ordered Al/Cr sub-lattice atom column intensities (dark).…”
supporting
confidence: 80%
“…The average width of the c regions between c 0 , also known as c channels, is 30-40 nm. Atomic-resolution EDS, in Figure 1(b), reveals that Cr predominantly occupies the Al sub-lattice in the c 0 phase, in agreement with recent atom probe tomography experiments 15,16 and first-principles calculations. 17 At the atomic scale, a representative c 0 /c interface is shown in Figure 1(c), where the two regions can be distinguished by the presence of the ordered Al/Cr sub-lattice atom column intensities (dark).…”
supporting
confidence: 80%
“…Cr, Hf and Zr substitute for the Al sublattice sites while Pt substitutes for Ni sublattice sites. Experimentally, it is observed that Cr substitutes preferentially at the Al sublattice sites [37] and other first-principles studies show the same results [12,13,37]. The site preference of Y in L1 2 $Ni 3 Al is not studied before but based on the same approach its preference for the Al sublattice sites is expected.…”
Section: Alloyssupporting
confidence: 55%
“…However, our experimental observations show that for the case of these precipitates created using a cooling rate of 10K/min, Al content of γ increases as the precipitates get smaller, from 12.5 at.% in secondary γ precipitates with diameters of ∼230 nm, to 15.5 at.% in the smallest tertiary γ (∼25 nm). In contrast, the experimentally measured 25 and Ni 74 Al 26 , respectively. All data has been extended from 6.7 × 10 −4 K −1 (1500 K) to 13 × 10 −4 K −1 (770 K) using Arrhenius curves and assumes a dilute solid solution.…”
Section: -P2 Eurosuperalloys 2014contrasting
confidence: 42%
“…For the more complex case of RR1000 nickel-based superalloy, the chemistry of the γ phase is generally given as (Ni, Co, Cr, Mo) 3 (Al, Ti, Ta, Hf. The elements Al, Ti, Ta and Hf, are generally assumed to substitute into the β-sublattice, while Ni, Co, Cr, and Mo occupy the α-sublattice as predicted by first principle calculations [20][21][22][23][24][25]. Herein Hf is not found to be present at measurable levels in the precipitate size range considered in this work.…”
Section: Experimental Approachesmentioning
confidence: 77%